Measuring Service Quality of a Multi-Disciplinary Engineering Course - Git, H. M. (2010)
A non-traditional engineering design course for undergraduates is introduced to simulate multi-disciplinary team setting in actual working environment. In the course, students of various engineering disciplines work in groups of six, to develop conceptual prototypes using fundamental engineering knowledge under the supervision of lecturers. With enrolment of about 500 students in every semester, effective administration is crucial in ensuring satisfactory operation of the course. Furthermore, the involvement of large numbers of lecturers, and academic departments increases the complexity of the course management. To ensure smooth operation of the course, it is important for the course coordinators to be able to measure the quality of the services provided to the students based on the level of their satisfaction. The present paper demonstrates the use of SERVQUAL as an effective approach to measure the service quality of the course. The study is done empirically by analyzing the difference between expectations and perceptions of the students, vis-à-vis service quality. The outcome of the analysis would enable identification of the scope of future improvement in the aspect of administration of the course. From the reliability testing, the items within the quality dimensions are found to measure the same attribute as intended, and thus, satisfactorily indicate the reliability of SERVQUAL for quantification of service quality. The findings from the present study as well as those in the future would be useful indicators for the course coordinators to achieve sustained satisfaction among the students in the course.